Sodium-based chitosan polymer embedded with copper selenide (CuSe) flexible film for high electromagnetic interference (EMI) shielding efficiency - Osman, Nurul Huda; Mazu, Nurul Najiha; Liew, Josephine Ying Chyi; Ramli, Muhammad Mahyiddin; Sandu, Andrei Victor; Nabiałek, Marcin; Mohd Abdull Majid, Mohammad Abdull Halim (MDPI, 2021)
Efficient shielding materials are extremely important to minimize the effect of electromagnetic interference. Currently, various composite materials are being investigated with different shielding efficiencies reported. In this paper, a flexible and free-standing sodium-based chitosan (CH/Na) polymer with copper selenide (CuSe) filler was prepared for electromagnetic shielding. The CH/Na/CuSe polymer matrix was prepared via the direct casting technique at different wt% of CuSe, varying from 2 to 20 wt%. The polymer matrix was then characterised by using Fourier transform infrared (FTIR) spectroscopy to confirm the interaction between the CH/Na and CuSe. The XRD results revealed that the CH/Na/CuSe polymer was successfully formed. Improvement in the electrical conductivity was confirmed by an impedance spectroscopy measurement. The highest electrical conduction recorded was at 3.69 × 10−5 S/cm for CH/Na/CuSe polymer matrix with 20 wt% CuSe. An increase in total electromagnetic interference (EMI) shielding efficiency (SET) of up to 20 dB (99% EM power shield) was achieved, and it can be increased up to 34 dB (99.9% EM power shield) with the thickness of the polymer increased.